What is the role of ESG in value relevance? A comparison of the evidence in Latin America before and during the pandemic of COVID-19 - Santos, Geovane Camilo dos; Tavares, Marcelo (Advances in Scientific and Applied Accounting, 2023)
Objective: to analyze the value relevance of environmental, social, and corporate governance (ESG) performance by comparing the period before and during the pandemic. Method: the sample consists of 1,937 observations from six Latin American countries in the sample period 2010-2021. The data were collected from Refinitiv Eikon® and treated by Ordinary Least Squares (OLS) and Generalized Method of Moments (GMM) panel data. Results: show that the ESG variable had a significant and negative relationship with the stock prices for the overall analysis (2010-2021) using the OLS model, while in the GMM model, the relationship was positive. OLS panel analysis indicated no significant relationship both before and during the pandemic. The results in the GMM model (reference in this research for the endogeneity control) allow us to conclude that investors in Latin American companies are considering ESG performance information, especially during the pandemic, as a relevant factor for their decision-making process, according to the Stakeholder Theory. Contribution: can contribute to investors by showing that ESG performance in Latin America is relevant, as it can positively affect stock prices. Managers also have signs that higher ESG performance can create value for the organization. Thus, investors and managers know that the higher the ESG performance, the higher tends to be the stock price. The study can also contribute to researchers by highlighting that endogeneity problems need to be considered in value relevance models.